Formation, Transformation, and Electrical Performance of Magnéli Phases Obtained by Flame Spraying from TiO2 Particles (2024)
ABSTRACT: In this paper, the formation and transformation of Magne ́li phases (TinO2n-1) during manufacturing of flame-sprayed coatings from two powders consisting of anatase nanoparticles and submicrometric particles with Magne ́li phases is analyzed, respectively. These powders were thermally sprayed on a ceramic substrate through oxidizing and neutral flame. Crystalline phases in powders and coatings were identified by x- ray diffraction and quantified by the Rietveld method, verifying the presence of identified crystalline phases in coatings by x-ray photoelectron spectroscopy. Finally, the electrical conductance of coatings was measured by the four-point probe method. Results indicate that Magne ́li phases are produced from anatase nanoparticles sprayed using both the oxidizing and neutral flames, and when the neutral flame and finest particles are used, a high quantity of Ti4O7 and Ti5O9, recognized thanks to their high electrical conductivity, is obtained. In contrast, when the coatings were fabricated from the powder containing Magne ́li phases, they were oxidized as much in oxidizing as in neutral flame, producing a partial transformation from Ti4O7 and Ti5O9 to both the rutile phase and TiO in low quantity. In spite of this partial transformation, the coatings maintain high electrical conductivity thanks to Ti4O7 and Ti5O9 Magne ́li phases remaining and the TiO produced.